2004
DOI: 10.1142/s0217732304011466
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Acoustic Waves on Coherent Bremsstrahlung in Crystals

Abstract: We investigate the coherent bremsstrahlung by relativistic electrons in a single crystal excited by hypersonic vibrations. The formula for the corresponding differential cross-section is derived in the case of a sinusoidal wave. The conditions are specified under which the influence of the hypersound is essential. The case is considered in detail when the electron enters into the crystal at small angles with respect to a crystallographic axis. It is shown that in dependence of the parameters, the presence of h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…From the point of view of controlling the parameters of various radiation processes in a medium, it is of interest to investigate the influence of external fields, such as acoustic waves, temperature gradient etc., on the corresponding characteristics. The considerations of processes, such as diffraction radiation, 20,21 parametric Xradiation, 22 channeling radiation, [23][24][25][26][27][28][29] bremsstrahlung of high-energy electrons, 30,31 electron-positron pair creation by high-energy photons, 32,33 have shown that the external fields can remarkably change the spectral and angular characteristics of the radiation intensities. Recently there has been broad interest in compact crystalline undulators with periodically deformed crystallographic planes as an efficient source of high energy photons [34][35][36][37][38][39][40][41][42][43] (for a review see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of controlling the parameters of various radiation processes in a medium, it is of interest to investigate the influence of external fields, such as acoustic waves, temperature gradient etc., on the corresponding characteristics. The considerations of processes, such as diffraction radiation, 20,21 parametric Xradiation, 22 channeling radiation, [23][24][25][26][27][28][29] bremsstrahlung of high-energy electrons, 30,31 electron-positron pair creation by high-energy photons, 32,33 have shown that the external fields can remarkably change the spectral and angular characteristics of the radiation intensities. Recently there has been broad interest in compact crystalline undulators with periodically deformed crystallographic planes as an efficient source of high energy photons [34][35][36][37][38][39][40][41][42][43] (for a review see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This motivates the importance of investigations for various mechanisms of controlling the radiation parameters. In [5] we have discussed the influence of hypersonic waves excited in a crystal on the process of the bremsstrahlung of highenergy electrons. To have an essential influence of the acoustic wave high-frequency hypersound is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Usually this type of waves is excited by high-frequency electromagnetic field through the piezoelectric effect in crystals with a complex base. In the paper [8], we have generalized the results of [5] for crystals with a complex base and for acoustic waves with an arbitrary profile. For the experimental detection of final particles in the process of coherent bremsstrahlung it is important to know their angular distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the effect o f acoustic waves was studied w ith respect to the coherent bremsstrahlung radiation [ 1,2], coherent electron-positron pair production in a crystal [3,4], diffraction of free photons [5,6], X-ray transition radiation [7], and param etric X-ray (PXR) generation [8][9][10][11][12][13].…”
mentioning
confidence: 99%